Regenerative Braking in Electric Vehicle Using Quadratic Gain Bidirectional Converter. (31st January 2022) - Kumar, Mukesh; Singh, Kumar Abhishek; Chaudhary, Kalpana; Saket, R. K.; Khan, Baseem
Abstract : The manuscript proposes a quadratic gain bidirectional converter (QGBC). The proposed converter is operated in two different stages—step-up (motoring) and step-down (regenerative braking)—which can be employed in electric vehicle (EV) applications. The converter is operated in the continuous inductor current mode (CICM). For regenerative braking (RB) of permanent magnet brushless DC (PMBLDC) motor, the self-inductance of the motor is exploiting to step up the back electromagnetic force (EMF) of the motor to extract the energy even at low rotor speed. The design parameters of the converter are selected as battery voltage V s = 48 V, output voltage V o = 200 V, output power P o = 1 kW, and switching frequency f s = 20 kHz . The design system is simulated using MATLAB/Simulink. Finally, a 1 kW prototype is developed for validation and performance analysis of the converter. The converter operates at maximum efficiency of 95% during step-up operation of the converter. A DSP microcontroller TMS320F28335 is used to control the switches of the converter in the experimental setup.